Clear and Simple as the Truth Writing Classic Prose - Thomas, Francis-Noël (Princeton University Press, 2017)
These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905
Description based on online resource; title from PDF title page (publisher's Web site, viewed 13. Sep 2017)
Keywords: English language -- Rhetoric; English language -- Style; Report writing; Stilistik; Englisch; Lehrbuch